Linguistic images in A.S. Pushkin’s travelogue «Journey to Arzrum» - Bezzubikova, M. V.; Piavrai, Sh (Vestnik Samarskogo universiteta. Istorii͡a︡, pedagogika, filologii͡a, 2022)
The discursive-cognitive nature of the linguistic image includes: (a) a subject-sensory representation (the cognitive substrate of the phenomenon), (b) a figurative word acting as its verbal exponent (c) a discursive-associative architectonics of the communicative-event meanings of the concept projecting the corresponding linguistic image. Narrative discourse plays a special role in creating a linguistic image. In this speech-thinking environment, an image-generating context is formed with the effect of the presence of the narrator. The main idea is that narrative discourse provides the ability to convey a subjective vision of the experienced fragments of a communicative event with the help of a linguistic image. Discursive expansion fills symbolic concepts with autochthonous images and reveals in travel essays a rich and multifaceted palette of the eastern worldview. The extraction of ethno-cultural meanings is based on the selected components of the linguistic image. Ethnocultural meanings serve to create a picturesque exotic flavor in A.S. Pushkins travelogue Journey to Arzrum.